Clinical experience of vasoepididymostomy using a triangulation technique - Hibi, Hatsuki (Reprod Med Biol, 2003)
Background: Although the number of patients receiving vasoepididymostomies is gradually increasing, these individuals are limited in the recent advanced assisted reproductive technology (ART) era. A novel technique involving vasoepididymostomy with epididymal tubular invagination has been reported. We attempted to define the results of this method and to compare them with the conventional end‐to‐side technique in patients with suspected epididymal obstruction and no previous history of vasectomy. Methods and Results: Eight eligible triangulation end‐to‐side vasoepididymostomy procedures performed on five azoospermic patients exhibiting either unilateral or bilateral epididymal obstruction are described. The overall patency rate following operation was 100% (five of five). Two pregnancies were achieved by natural intercourse and one was accomplished via artificial insemination. A single pregnancy was obtained with an intracytoplasmic sperm injection using frozen‐thawed sperm collected during the operation. Conclusion: Vasoepididymostomy, using the triangulation technique for epididymal obstruction, resulted in an earlier patency in all patients. This method may afford advantages when compared with the conventional end‐to‐side approach; however, larger subject populations are required in order to assess further the efficacy of this procedure. In addition, long‐term follow up is necessary. (Reprod Med Biol 2003; 2: 101–104)